LOCATION SUITABILITY AND PERFORMANCE OF FRESHWATER FISH FARMING IN FLOATING NET CAGES AT THE PAMARAYAN DAM, SERANG, BANTEN - Wahyu Hidayat; Adi Susanto; Desy Aryani (Jurusan Perikanan dan Kelautan, 2023)
The Pamarayan Dam is located in Cikeusal District, Serang Regency, Banten Province where many freshwater fish cultivators based on floating net cages are found. Important aspects that are assessed in aquaculture activities are measuring water quality, location suitability, and productivity. This study aimed to determine the site suitability criteria and analyze the existing performance of fish farming activities with floating net cages. The research was conducted from January to March 2023 at the Pamarayan Old Dam at 4 stations. Water sampling was carried out in situ and ex situ including temperature, pH, DO, TDS, current, brightness and depth, BOD, COD, total P, total N, TSS, and ammonia. Water quality analysis was carried out at the DLH laboratory in Serang City and UPT LABKES in Serang Regency. Additional data by conducting interviews with cultivators. The results showed that the Pamarayan Dam had suitability in the S2 class (appropriate) at all stations. This is based on water quality, most of which are still in accordance with class 3 quality standards including parameters of temperature, pH, BOD, TSS, DO, COD, total P, and ammonia. Cultivation performance at the Pamarayan Dam has a large advantage, where the average net profit per cultivation cycle is Rp. 41.332.000.